Tinjauan Sistematis Tentang Faktor Prediktor dan Dampak Kecemasan Sosial pada Remaja Korban Bullying - Eva Sulistyo; Suhadianto Suhadianto (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Bullying is a major issue affecting adolescents and contributes to various mental health problems, particularly social anxiety. Although numerous studies have examined the predictors and consequences of social anxiety among bullying victims, the available evidence remains fragmented. This study aimed to identify and synthesize the predictor factors and impacts of social anxiety among adolescent bullying victims using a Systematic Literature Review (SLR). Literature was retrieved from Google Scholar and Scopus databases following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. After applying predefined inclusion and exclusion criteria, 20 studies published between 2019 and 2025 were included in the review. The findings indicate that social anxiety is influenced by multiple predictor factors, including bullying and cyberbullying victimization, limited social support, low self-esteem, parenting style, assertive behavior, school environment, and individual characteristics. The most frequently reported impacts include social withdrawal, impaired interpersonal relationships, low self-confidence, depression, poor social adaptation, and reduced quality of life. These findings suggest that social anxiety among adolescent bullying victims results from the interaction of psychological and environmental factors. This review provides comprehensive evidence that may support the development of prevention strategies and mental health interventions for adolescents.